A COMPARATIVE STUDY OF LEGAL SYSTEMS AROUND THE WORLD: THEIR CHARACTERISTICS AND APPLICATION - Fauziah Hanum; Sukiati Sukiati; Iwan Iwan (Hukum tata Negara/Siyasah, 2026)
A legal system is a set of interrelated rules that serve to regulate society in order to establish order and justice. This paper aims to explain the concept of a legal system, the types of legal systems that have developed around the world, and a comparison of their application in several countries. The method used is a literature review that analyzes various concepts and theories regarding legal systems. The results of the discussion indicate that, generally, legal systems worldwide are divided into several main types, namely the European Continental legal system (civil law), the Anglo-Saxon legal system (common law), Islamic law, customary law, and mixed legal systems. Civil law emphasizes written law codified in statutes, whereas common law places greater emphasis on court decisions or precedents as the primary sources of law. Additionally, Islamic law is derived from the Quran and Hadith as well as the method of ijtihad in legal reasoning, while customary law arises from living traditions within society. In practice, many countries adopt a mixed legal system as a result of globalization and societal developments. Indonesia itself fundamentally adheres to the civil law system, but in practice is also influenced by customary law and Islamic law, thereby forming a pluralistic legal system.Keyword: legal system, civil law, common law, Islamic law, customary law